2021
DOI: 10.1186/s12910-021-00584-9
|View full text |Cite
|
Sign up to set email alerts
|

Health workers’ perspectives on informed consent for caesarean section in Southern Malawi

Abstract: Objective Informed consent is a prerequisite for caesarean section, the commonest surgical procedure in low- and middle-income settings, but not always acquired to an appropriate extent. Exploring perceptions of health care workers may aid in improving clinical practice around informed consent. We aim to explore health workers’ beliefs and experiences related to principles and practice of informed consent. Methods Qualitative study conducted betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(58 citation statements)
references
References 38 publications
4
51
0
Order By: Relevance
“…According to previous studies, possible reasons that can contribute to the delay of obtaining consent for CS include delays in patient preoperative preparation, delays in the preparation of surgical kits, delays in the transfer of the patient from the ward to the operating theatre, delays in being able to pay the required surgical fees, lack of money to buy surgical kits, and delayed decision-making on the part of families [ 22 , 27 ]. Healthcare providers need to be trained to have adequate skills on how to communicate and effectively seek consent from their patients and family members and motivate them to make a prompt decision when there is a need for an emergency procedure such as a CS [ 28 ]. Our study highlights that interventions related to improving the quality of the informed consent process, as implemented in other contexts with delayed CS [ 29 ], would facilitate a shorter interval between decision to perform a CS to delivery time, thereby reducing adverse maternal and newborn outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, possible reasons that can contribute to the delay of obtaining consent for CS include delays in patient preoperative preparation, delays in the preparation of surgical kits, delays in the transfer of the patient from the ward to the operating theatre, delays in being able to pay the required surgical fees, lack of money to buy surgical kits, and delayed decision-making on the part of families [ 22 , 27 ]. Healthcare providers need to be trained to have adequate skills on how to communicate and effectively seek consent from their patients and family members and motivate them to make a prompt decision when there is a need for an emergency procedure such as a CS [ 28 ]. Our study highlights that interventions related to improving the quality of the informed consent process, as implemented in other contexts with delayed CS [ 29 ], would facilitate a shorter interval between decision to perform a CS to delivery time, thereby reducing adverse maternal and newborn outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, during obstetric emergencies (i.e., IVB, CS and even more emergency CS), it may be impossible to disclose all potential risks and complications of those procedures without bias (“framing effect” when clinicians intentionally may frame information provided toward the outcome preferred by them) that might hinder women’s autonomy [ 24 , 37 , 41 , 46 , 60 ]. Therefore, future research should explore the effectiveness of alternative ways to provide informed consent for emergency procedures that may include timely consultation and better patient information during antenatal care courses with the support of videos, simulations and multimedia tools.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review including 15 studies reported that in Ethiopia, 16% to 92.5% of women did not provide a written and verbal informed consent before any procedure during labour and birth [ 22 ], while another study from Kenya documented that over 60% of women reported not consenting to newborn procedures [ 23 ]. In addition, few studies have reported challenges or barriers to the informed consent process in the maternal and newborn care area from health workers’ perspectives [ 24 , 25 ]. In Italy, according to the Physicians’ Deontological Code [ 26 ], consent request is a non-delegable physicians’ act.…”
Section: Introductionmentioning
confidence: 99%
“…A Malawian study found that HCPs took the time to use simple language to counsel women and ask women to paraphrase to check understanding. 24 This helped overcome barriers to communication posed by A Nigerian study found 78% of women felt their doctors listened to their worries, compared with 40% who felt the same about nurses. 39 In Tanzania, post-cesarean women participating in a study reported midwives did not adequately communicate with them and address their concerns.…”
Section: Verbal Explanationmentioning
confidence: 99%
“…Language differences between women and their HCPs was a key communication barrier identified in this review. 24,26 It was found that poorly designed consent forms only exacerbated this issue as they were not inclusive of all native languages. 24,30 The purpose of a consent form is to facilitate the informed consent process by ensuring the patient has received full disclosure of information, provided by HCPs in a systematic fashion, with adequate time to ask questions.…”
Section: Barriersmentioning
confidence: 99%